Parâmetros polissonográficos e respostas cardiorrespiratórias ao teste de esforço máximo em idosos hipertensos com apneia obstrutiva do sono - Barbosa, Bruno Teixeira (2016)
Elderly have a high prevalence for the systemic arterial hypertension (SAH) and obstructive sleep apnea syndrome (OSAS); both comorbidities are closely associated and inflict injury cardiorespiratory capacity (CCR). In spite of studies demonstrating that OSAS promotes a loss into the cardiorespiratory responses along some effort test, and in hypertensive triggers hypertensive response, we still do not know whether the OSAS in elderly with SAH adds this dysfunction CCR. Therefore, we will assess the cardiorespiratory responses to the cardiopulmonary exercise test (CPT), sleep quality and heart rate recovery (HRR) among hypertensive elderly (HE) with OSAS; and we will check whether there is correlation between the apnea/hypopnea index (AHI) and/or the oxygen saturation/desaturation (SatO2/DSatO2) during sleep with the CPT variables. We had evaluated 25 HE from both sex, they were divided into two groups: without OSA (SAH: AHI < 5; n = 13) and with OSAS (SAH+OSAS: AHI ≥ 15; n = 12). All of them underwent anthropometric assessment, CPT, polysomnography and echocardiography and they have answered to a questionnaire about their sleep quality. The Chi-squared test was used to compare the proportions of men and women and classes of antihypertensive drugs. The normality and homoscedasticity of data were determined using the Shapiro-Wilk and Levene tests, respectively. Anthropometric and echocardiographic, sleep, CPT parameters and age were analyzed by the Mann-Whitney test. The Spearman correlation test was used to evaluate the association between cardiorespiratory parameters of the CPT (VO2, PuO2, RER, VEpeak, VE/VCO2, ΔHR/ΔVO2, VO2/ΔWR, blood pressure and heart rate (HR)) with the AHI and SatO2/DSatO2. The significance level was p < 0.05. There were significant differences in sleep architecture, characterized by greater periods of sleep and total sleep time in SAH+OSAS in relation to SAH (p < 0.05). About the CPT, both groups have showed similar workload (SAH: 78 (66-96) W/min; SAH+OSAS: 85 (47-114) W/min, cardiorespiratory variables and systolic blood pressure (p > 0.05). On the other hand, SAH+OSAS presented lower HRR2min in relation to SAH. In the correlation analysis we did not verify any association between AHI with CPX variables. However, we have observed correlation between DSatO2 and HRR1min (p = 0.01; r = -0.481); between SatO2 with VEpeak (p = 0.04; r = 0.398) and with maximum heart rate (HRmax) (p = 0.04; r = 0.412) and HRR in the first and second minutes (p < 0.01; r = 0.572; p = 0.02; r = 0.450, respectively). The OSAS seems not to prejudice the cardiorespiratory responses in HE; but attenuates the HRR2min. The association between the SatO2/DSatO2 during the sleep with the ventilatory and cardiac responses at the CPT is probably due to cardiac autonomic dysfunction and to adjustments caused by aging in respiratory function.